Crowdfunding practices in higher education institutions in Malaysia: the case of Universiti Teknologi MARA Cawangan Melaka (UiTMCM)/ Norajila Che Man… [et al.] - Che Man, Norajila; P. Rameli, Mohd Faizal; Abd Wahab, Nor Azlina; Jaapar, Nurzahidah; Rabu, Noormala (Center for Islamic Philantrophy & Social Finance (CIPSF), 2019)
Philanthropic crowdfunding or donation-based crowdfunding is one of the mediums that can be used by higher education institutions (IPT) to transform and empower students, faculty and staff by securing the funds for projects and initiatives that has been planned. Waqf and sadaqah are two instruments of philanthropic crowdfunding that commonly used in funding any activities or programs in IPT. Universiti Teknologi MARA Cawangan Melaka (UiTMCM) also engaged in crowdfunding practice to finance several projects that has been planned but being adjourned due to insufficient funds. On that notes, this paper investigates the practices of crowdfunding in higher education institutions specifically in UiTMCM. Also, this study examines challenges faced by these institutions that lead to the failure to fulfil the programs that have been planned. Data and information for this study are collected through a semi-structured interview method with four respondents in UiTMCM and reference to the primer and secondary documents. Content analysis method were used in analysing the data. The finding indicates that UiTMCM used Waqf as their instruments of crowdfunding. This instrument of crowdfunding has been proved in helping UITMCM to solve financial shortage without depends solely from the management funds. Furthermore, people are willing to donate for a good purpose.